Staphylococcus Aureus - Hemeg, Hassan; Ozbak, Hani; Afrin, Farhat (IntechOpen, 2019)
Staphylococcus aureus strains are an important medical infectious agent that causes a wide range of pathogeneses starting from colonization of the skin and mucosal surface to severe pathogenic effects such as septicemia. The mortality and morbidity from this pathogen are challenging issues for the healthcare premises. Methicillin Resistant Staphylococcus aureus strains (MRSA) are causing severe infections due to the genes that are resistant to several antibiotics including methicillin, aminoglycosides, and others. Recently, there have been several reports related to failure of treatment plans caused by MRSA that led to Vancomycin Intermediate Staphylococcus aureus strains (VISA) or, in sporadic cases, resistance to the drug of choice. This book highlights the new areas for the treatment of MRSA using natural products. The implementation of specific products produced by this organism can help the scientist to obtain a new window for treatments such as anticancer chemotherapy, antioxidants, etc.